Dissolution of glass in cementitious solutions: An analogue study for vitrified waste disposal. (27th February 2018) - Mann, Colleen; Le Hoh, Tjin; Thorpe, Clare L.; Corkhill, Claire L.
Abstract : The dissolution of a soda-lime silicate glass in two cement leachate compositions, Young Cement Water (YCW) and Ca(OH)2, was investigated, as an analogue for dissolution of vitrified nuclear waste in a cementitious geological disposal facility. Dissolution was performed at repository temperatures (50°C) and under CO2 -exclusion. Dissolution rates were observed to be a factor of 20 times higher in YCW than in Ca(OH)2, as result of the high potassium content of YCW solutions. The precipitation of the zeolite phase, K-phillipsite (K(Si, Al)8 O16 ·6H2 O), is thought to be responsible for elevated dissolution rates. Conversely, in Ca(OH)2 solutions, the precipitation of calcium- and silica-containing phases, such as tobermorite (Ca5 Si6 O16 (OH)·4H2 O), acted to reduce rates of dissolution by forming a barrier to diffusion. These results show that dissolution of vitrified nuclear waste materials in a cementitous repository may be significant during the early stages of cement leaching in groundwater.